2012
DOI: 10.1021/bi201135s
|View full text |Cite
|
Sign up to set email alerts
|

The Diheme Cytochrome c Peroxidase from Shewanella oneidensis Requires Reductive Activation

Abstract: We report the characterization of the diheme cytochrome c peroxidase (CcP) from Shewanella oneidensis (So) using UV/Visible absorbance, Electron Paramagnetic Resonance Spectroscopy, and Michaelis-Menten kinetics. While sequence alignment with other bacterial diheme cytochrome c peroxidases suggests that So CcP may be active in the as-isolated state, we find that So CcP requires reductive activation for full activity, similar to the canonical Pseudomonas-type of bacterial CcP enzyme. Peroxide turnover initiated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
63
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(72 citation statements)
references
References 42 publications
8
63
0
1
Order By: Relevance
“…Intriguingly, glutathione peroxidase (SO3349 and SO1563), c-type cytochrome peroxidase (CcpA), and organic hydroperoxide resistance protein (Ohr), being OxyR SO dependent or not, are substantially upregulated when stimulated. These proteins function to degrade H 2 O 2 at the expense of NADPH, cytochrome c, and thiol, respectively, although their contribution to H 2 O 2 removal is negligible under the tested aerobic conditions (63)(64)(65). In the case of glutathione peroxidase and Ohr, this is not surprising, given that both proteins are reportedly irrelevant in the bacterial response to H 2 O 2 -induced oxidative stress.…”
Section: Discussionmentioning
confidence: 96%
“…Intriguingly, glutathione peroxidase (SO3349 and SO1563), c-type cytochrome peroxidase (CcpA), and organic hydroperoxide resistance protein (Ohr), being OxyR SO dependent or not, are substantially upregulated when stimulated. These proteins function to degrade H 2 O 2 at the expense of NADPH, cytochrome c, and thiol, respectively, although their contribution to H 2 O 2 removal is negligible under the tested aerobic conditions (63)(64)(65). In the case of glutathione peroxidase and Ohr, this is not surprising, given that both proteins are reportedly irrelevant in the bacterial response to H 2 O 2 -induced oxidative stress.…”
Section: Discussionmentioning
confidence: 96%
“…Shewanella oneidensis MR-1 is one of the most important DMRB species and has been extensively used to study the mechanisms underlying the respiration of insoluble substrates and electron transfer under aerobic and anaerobic conditions (Brutinel and Gralnick, 2012;Gao et al, 2010;Ross et al, 2009). In studies of Shewanella during the last two decades, a number of possible mechanisms for electron transfer at the microbe-mineral interface have been suggested: (i) the direct transfer of electrons to insoluble mineral substrates (Shi et al, 2012;Schütz et al, 2011), (ii) indirect electron transfer mediated by flavin electron shuttles (Ross et al, 2009;Covington et al, 2010;Marsili et al, 2008;Pulcu et al, 2012) or (iii) intercytochrome electron transfer, possibly along the ''nanowires'' discovered by Gorby et al (El-Naggar et al, 2010;Gorby et al, 2006;Reguera et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The protein components involved in the Mtr pathway include Cytochrome c (CymA) and Fe(III) reductase (including MtrA, MtrB, MtrC and OmcA) which are thought to control electron transfer. However, excluding the cytochrome c-type peroxidases and Fe(III) reductase (Schütz et al, 2011;Pulcu et al, 2012;Gescher et al, 2008), thorough enzymatic studies have rarely been reported. As enzymes of oxidoreductase are particularly sought for the degradation of dyeing effluents as their specificity and characterization on attack dyes, the identification and exploration of individual redox-active enzymes makes a discernible contribution to degradation of toxicity compounds and bioremediation potential.…”
Section: Introductionmentioning
confidence: 99%
“…Recombinant Shewanella oneidensis cytochrome c peroxidase was expressed and purified in the same manner as in the recent paper from Pulcu et al (18). Similarly, the recombinant So c 5 (gene SO0264/plasmid pSOc5) was expressed and purified as previously by Pulcu et al (18).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, the recombinant So c 5 (gene SO0264/plasmid pSOc5) was expressed and purified as previously by Pulcu et al (18). So CcP mutants, E258K and E321K, were constructed using the QuikChange Mutagenesis Kit and expressed and purified as an MBP fusion as described for wild-type enzyme.…”
Section: Methodsmentioning
confidence: 99%